##### 4.17.30 $$x^4 y(x)^4-x \left (x^2+y(x)^2\right ) y(x) y'(x)+y'(x)^2=0$$

ODE
$x^4 y(x)^4-x \left (x^2+y(x)^2\right ) y(x) y'(x)+y'(x)^2=0$ ODE Classiﬁcation

[_separable]

Book solution method
No Missing Variables ODE, Solve for $$y'$$

Mathematica
cpu = 0.246144 (sec), leaf count = 55

$\left \{\left \{y(x)\to -\frac {1}{\sqrt {-x^2-2 c_1}}\right \},\left \{y(x)\to \frac {1}{\sqrt {-x^2-2 c_1}}\right \},\left \{y(x)\to c_1 e^{\frac {x^4}{4}}\right \}\right \}$

Maple
cpu = 0.062 (sec), leaf count = 38

$\left [y \left (x \right ) = \frac {1}{\sqrt {-x^{2}+\textit {\_C1}}}, y \left (x \right ) = -\frac {1}{\sqrt {-x^{2}+\textit {\_C1}}}, y \left (x \right ) = \textit {\_C1} \,{\mathrm e}^{\frac {x^{4}}{4}}\right ]$ Mathematica raw input

DSolve[x^4*y[x]^4 - x*y[x]*(x^2 + y[x]^2)*y'[x] + y'[x]^2 == 0,y[x],x]

Mathematica raw output

{{y[x] -> -(1/Sqrt[-x^2 - 2*C[1]])}, {y[x] -> 1/Sqrt[-x^2 - 2*C[1]]}, {y[x] -> E
^(x^4/4)*C[1]}}

Maple raw input

dsolve(diff(y(x),x)^2-x*y(x)*(x^2+y(x)^2)*diff(y(x),x)+x^4*y(x)^4 = 0, y(x))

Maple raw output

[y(x) = 1/(-x^2+_C1)^(1/2), y(x) = -1/(-x^2+_C1)^(1/2), y(x) = _C1*exp(1/4*x^4)]